Initial forms of radio broadcasting communications in Ukraine in the 1930s - Nahorniak, Mayya V. (Journal of the Belarusian State University. Journalism, 2019)
The emergence of radio communication in Ukraine in the 1930s was marked by the production of a number of forms of communion the ordinary listener to familiarize with the information from different spheres of public life. Examines the nature, structure, ideological orientation of the most expressive forms of communication. It is proved that radio newspaper for all without an exception of categories of the original population, talk radio, radiomeeting, radio talk film became the primary manifestation of the feedback from the listening audience. Presents the author’s vision of the laws of transformation of the original form of radio communication in the interactive activities of the current Ukrainian radio stations. The widespread use of the principles of communication with listeners in 1930s has, no doubt, to diversify the genre palette of the domestic radio of the new sample.